(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2021)
This work presents some notes are aimed at analyzing the origins, conditions and consequences of the presence of Venezuelans as veterinary students in Spain at the beginning of the second half of the 20th century; it is a contribution to the history of the profession and to the understanding of a moment particular of the social, academic and professional dynamics of Venezuela.